The inter-related dynamics of dual job holding, human capital and occupational choice - Georgios A. Panos; Konstantinos Pouliakas; Alexandros Zangelidis (Institute for the Study of Labor (IZA), 2009)
The inter-related dynamics of dual job-holding, human capital and occupational choice between primary and secondary jobs are investigated, using a panel sample (1991-2005) of UK employees from the British Household Panel Survey (BHPS). A sequential profile of the working lives of employees is examined, investigating, first, the determinants of multiple job-holding, second, the factors affecting the occupational choice of a secondary job, third, the relationship between multiple-job holding and job mobility and, lastly, the spillover effects of multiple job-holding on occupational mobility between primary jobs. The evidence indicates that dual job-holding may facilitate job transition, as it may act as a stepping-stone towards new primary jobs, particularly self-employment.
urn:nbn:de:101:1-200910141167
Keywords: J22; J24; J62; 330; Moonlighting; occupational choice; human capital; mobility; Nebentätigkeit; Schwarzarbeit; Berufswahl; Arbeitsmobilität; Humankapital; Großbritannien